FINANCIAL KNOWLEDGE AND ITS REFLECTION ON FINANCIAL BEHAVIOR: AN ANALYTICAL STUDY OF A SAMPLE OF CUSTOMERS WITH THE TBI, RAFIDAIN & RASHEED BANKS (American Journal of Business Management, Economics and Banking, 2023)
The research aims to determine the role of financial knowledge among the research sample, which is represented by the employees and professors of the College of Administration and Economics - the University of Kufa and the College of Imam Al-Kadhim, As they are part of the society that participates in the use of finance at the level of daily consumption and continuous financial transactions. They are in the field of our current study, which is concerned with matters related to economics and finance, which should add better value to financial knowledge and its nature. Therefore, college staff needs to know and apply the meaning of personal financial management to be able to manage their financial affairs and live more prosperously in the future. There is a growing gap between the amount of financial responsibility given to individuals and their apparent ability to manage financial decisions and take advantage of financial opportunities. Therefore, the study was conducted on those who deal with Al-Rasheed and Al-Rafidain Bank and TBI by taking all the dealers with these banks as a sample population, 120 questionnaires were distributed and 116 approved questionnaires were answered by the employees of the two colleges, the method was applied using SPSS version 23. The conclusion was that financial knowledge has a positive and significant impact on personal financial behavior and as well as financial knowledge has a positive and significant impact on the personal financial management of the study sample individuals.